Implications of cytokine genes polymorphisms in Jordanian patients with obsessive compulsive disorder - Ahmad M. Khalil; Manal W. Khrais; Khaled M. Al-Qaoud; Mohamad Y. Al Ta’any (Egyptian Journal of Medical Human Genetics)
Abstract Background Obsessive–compulsive disorder (OCD) is a common and often highly debilitating chronic neuropsychiatric condition. There is substantial evidence that immune system and genetic changes are involved in OCD pathogenesis. Only a few studies have been encountered in the literature in this field. We aimed at providing experimental evidence for single nucleotide polymorphisms (SNPs) in candidate cytokine genes for the etiology of OCD. Methods A total of 52 OCD patients and 54 healthy controls were randomly recruited from the Jordanian population. Age ranged between 16 and 55 years (35.5 ± 13.72 and 33.5 ± 10.48 years) for patients and controls, respectively. Five polymorphic positions in four interleukin genes (IL-1β; rs16944 and rs1143634, IL-6; rs1800795, IL-10; rs1800896 and rs1800795) were genotyped using polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) method. The tumor necrosis factor-α (TNF-α) SNP (rs1800629) DNA was sequenced by the Sanger method. The obtained data were analyzed using the GraphPad Prism method. Results There were no statistically significant differences between the alleles and genotypes in opposite groups. However, there was a positive association between the incidence of the studied SNP cytokine genes in OCD patients and non-OCD individuals. The alleles of two SNPs (IL-1β + 3954 C > T and TNF-α-308 G > A) were more predominant and more positively correlated with a higher risk in OCD women. In contrast, the link between the gender and the occurrence of the mutant alleles of the other four SNPs IL-1β (− 511 C > T); IL-6 (− 174 G > C); IL-10 (− 1082 A > G); and IL-10 (− 819 C > T was more robust in the males OCD patients than the corresponding females. Conclusion The observed differences between the alleles in different groups may be due to an association in the tested samples rather than a true association. But, the possibility of a critical effect still exists. One might want to explore this further by repeating the study with a larger sample size.